2015
DOI: 10.12998/wjcc.v3.i7.575
|View full text |Cite
|
Sign up to set email alerts
|

Role of quorum sensing in bacterial infections

Abstract: Quorum sensing (QS) is cell communication that is widely used by bacterial pathogens to coordinate the expression of several collective traits, including the production of multiple virulence factors, biofilm formation, and swarming motility once a population threshold is reached. Several lines of evidence indicate that QS enhances virulence of bacterial pathogens in animal models as well as in human infections; however, its relative importance for bacterial pathogenesis is still incomplete. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(117 citation statements)
references
References 199 publications
0
115
0
2
Order By: Relevance
“…In our context, two hypotheses could be then issued: 1) the signal is recognized by each bacteria individually, changing their lipid metabolism tightly in relationship with toxin production (50); and 2) the environment established by the host disturbs/modifies the bacterial quorum sensing. Consequently, the bacterial community coordinately modified its metabolism and some gene expression, including for virulence factors, as described for various microorganisms (51)(52)(53)(54)(55).…”
Section: Bacilli Side Perspectivementioning
confidence: 99%
“…In our context, two hypotheses could be then issued: 1) the signal is recognized by each bacteria individually, changing their lipid metabolism tightly in relationship with toxin production (50); and 2) the environment established by the host disturbs/modifies the bacterial quorum sensing. Consequently, the bacterial community coordinately modified its metabolism and some gene expression, including for virulence factors, as described for various microorganisms (51)(52)(53)(54)(55).…”
Section: Bacilli Side Perspectivementioning
confidence: 99%
“…Several screenings have shown that natural products, particularly phytochemicals, are an interesting source of quorum sense inhibitor (QSI) (Castillo-Juárez et al, 2015). They have been recognized as a large and attractive repository of QSI, offering a vast chemical diversity with structural complexity and biological activity (Borges et al, 2015).…”
Section: Antibiofilm Activity Of Natural Substancesmentioning
confidence: 99%
“…P. aeruginosa infections can lead to skin complications but this bacterium is more notorious for being associated with the lung disease known as cystic fibrosis [76,77]. In order to establish a disease, P. aeruginosa contains canonical QS systems to control the expression of a plethora of virulence factors [1,4,78]. This bacterium contains three QS systems, with the main one being LasI/LasR, which is a homologue of the LuxI/LuxR system described in the Vibrio species.…”
Section: • Staphylococcus Aureus and Host-cell Vacuolesmentioning
confidence: 99%